Does Mood Explain the Monday Effect?. (7th July 2014) - Abu Bakar, Azizah; Siganos, Antonios; Vagenas‐Nanos, Evangelos; Breitner, Michael H.; Dunis, Christian; von Mettenheim, Hans-Jörg; Neely, Christopher; Sermpinis, Georgios
ABSTRACT A number of studies have explored the sources of the Monday effect, according to which returns are on average negative on Mondays. We contribute to the literature by exploring whether a direct measure of mood explains the Monday effect. In line with psychological literature, a greater proportion of investors are more pessimistic in the early days of the week, and become more optimistic as the week progresses. We use novel daily mood data from Facebook across 20 international markets to explore the impact of mood on the Monday anomaly. We find that the Monday effect disappears after controlling for mood. In line with our hypothesis that mood drives the Monday effect, we find that the effect is more prominent within small capitalization indices and within collectivist and high‐uncertainty‐avoidance countries. Investors could consider mood levels to forecast Mondays with more (less) pronounced negative returns. Copyright © 2014 John Wiley & Sons, Ltd.